Chemical Anchor Pullout Force Modeling with Variation of Anchor Embedment Length in Concrete and Concrete Strength - Rosyidah, Anis; Widiana Putra, Jasun; Saputra, Jonathan (Journal of the Civil Engineering Forum, 2022)
The embedment length influences the adhesion between the cast iron material and the concrete. The concrete’s compression strength also contributes to an increase in bond strength. Therefore, this research aims to determine the maximum pullout force on each variation of the anchor and the optimal embedment length. A gauge is modeled as a rod-type with a diameter of 16 mm, and the embedment lengths used are 5D, 10D, and 15D, while the compressive strengths include fc’ 20, 30, 40, 50, and 60 MPa. Furthermore, a finite element-based application was utilized with the ANSYS Workbench student version. The result showed that the concrete with strengths of 20, 30, 40, 50, and 60 MPa has maximum pullout forces of 27.011, 53.536, 68.657, 68.970, and 84.407 kN, respectively at an embedment length of 15D. It was observed that the failure pattern obtained starts from the defect in the concrete cone and ends with the breakage of reinforcement or steel failure at each variation of concrete strength. A combination of two non-parametric techniques was used in this research, which includes Kruskal Wallis and U-Mann Whitney test. The first technique revealed that the chi-square value for strengths 20, 40, 50, and 60 MPa is 9.486, while that of 30 MPa is 9.881. The second test employed showed a significance value below 0.05. In conclusion, the embedment length affected the value of pullout force, and 15D was the optimum embedment length for each variation of concrete strength. The enhancement in tensile strength increases with the strength of the concrete.